Factors Influencing Intention to Adopt Online Journalism Among Journalists in Iran - Varzandeh, Somayyeh (2011)
This study focused on influential factors toward adoption of online journalism among journalists. The study was conducted to determine 1) the influence of perceived ease of use and usefulness on attitude to adopt online journalism; 2) the influence of colleagues on subjective norms to adopt online journalism; 3) the influence of self-efficacy, prior computer experience, access to technological facilities, training and computer anxiety on perceived behavioral control; 4) the influence of attitude, subjective norm and perceived behavioral control on behavioral intention to adopt online journalism; 5) the mediating influence of attitude, subjective norm and perceived behavioral control in the relationship between independent variables (IVs) and behavioral intention (DV) to adopt online journalism; 6) the influence of demographic characteristics of journalists on behavioral intention to adopt online journalism. The questionnaire survey was employed as the instrument for data collection in this study. Purposive non-probabilistic sampling method technique was applied in the sample selection of the respondents. A self-administered questionnaire was designed as a research instrument in survey section. A total of 547 professional journalists participated in the survey conducted in the national and international daily newspapers in Iran. The return response rate was 83 percent. Statistical techniques engaged in survey study included frequency distribution, descriptive analysis statistics, t-test, one way analysis of variance (ANOVA), Pearson Correlation coefficient, multiple regressions and Baron and Kenny model. Based on the finding the result showed that perceived usefulness and ease of use positively affect attitude toward using online journalism. The findings also presented that the colleague’s influence is positively associated with subjective norm. It also identified perceived behavioral control is explained by independent variables (self-efficacy, facility condition, computer anxiety, prior experience, and training). Therefore all the five independent variables (self-efficacy, facility condition, computer anxiety, prior experience, and training) contribute significantly toward perceived behavioral control. Findings also showed that attitudes, subjective norm, and perceived behavioral control, significantly contribute to online journalism adoption intention. This study also indicated that attitude mediates the relationship between perceived usefulness, ease of use and behavioral intention. For the mediation effect of subjective norm, the results showed that subjective norm mediates the relationship between colleagues and intention to use online journalism. The results also found except for facility condition, perceived behavioral control mediates the relationship between the self-efficacy, computing experience, computer anxiety, training and intention to use online journalism. This study also showed that well-paid and better-educated males were more likely to be online journalism adopters. In addition, the journalists who were between 30 to 39 years old tended to use the online journalism more than others. The result also showed that there was no difference between journalists’ job positions in order to accept the online journalism.